2013
DOI: 10.1016/j.redox.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of somatic globins in cardiovascular redox biology and beyond

Abstract: The vertebrate globins are a group of hemoproteins with the intrinsic capacity to regulate gaseous ligands and redox signaling required for cardiovascular biology. This graphical review will provide a comprehensive synopsis of somatic cardiovascular globins focusing on expression, function and redox signaling – an emerging area in both physiology and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 71 publications
0
26
0
1
Order By: Relevance
“…Today, this paradigm in RBC remains unchanged. However we 3 , and others 4,5 , have demonstrated that Hbα is expressed in the blood vessel wall but in contrast to other globins in the blood vessel wall 3,6,7 , Hbα localization and physiological effects are concentrated at myoendothelial junctions (MEJs) in the endothelial cells (EC) lining the lumen of blood vessels.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Today, this paradigm in RBC remains unchanged. However we 3 , and others 4,5 , have demonstrated that Hbα is expressed in the blood vessel wall but in contrast to other globins in the blood vessel wall 3,6,7 , Hbα localization and physiological effects are concentrated at myoendothelial junctions (MEJs) in the endothelial cells (EC) lining the lumen of blood vessels.…”
Section: Introductionmentioning
confidence: 89%
“…Finally, excess NO may be scavenged by free hemoglobin alpha (Hbα) at the MEJ through reaction with oxyhemoglobin alpha (fast), or NO may be chelated through reaction with methemoglobin alpha (slow). Cytochrome B5 reductase (CyB5R3) converts methemoglobin alpha to Hbα, which readily binds oxygen 3,6,2123 .…”
Section: Figurementioning
confidence: 99%
“…In red blood cells, hemoglobin exists as a heterotetramer of two hemoglobin α (Hba) and two hemoglobin β (Hbb) subunits. However, studies have now shown that various cell types other than erythrocytes, such as macrophages, epithelial cells, and neurons, also contain hemoglobin (Rahaman and Straub 2013). The discovery of Hba and/or Hbb expression in diverse cell types suggests that they have other roles in addition to their role in O 2 and CO 2 transport.…”
Section: Introductionmentioning
confidence: 99%
“…Many single domain hexacoordinate Hbs have been associated with electron transfer rather than ligand transport [45]. Neuroglobin has links to cytochrome mediated apoptosis [46], NOD reactions [47][48][49][50], and nitrite reduction [22]. Cytoglobin uses lipid peroxidation [51] and auto-oxidation [45] as components of its function.…”
Section: The Role Of Ese In Hbs-mentioning
confidence: 99%